The Roles of Workplace Culture In The Relationship Between Performance Appraisal Effectiveness and Employee Outcomes - Lyvia Mannuela Sandra; SeTin SeTin (Jurnal Manajemen Teknologi, 2023)
Abstract. This study aims to examine the effect of performance appraisal effectiveness on employee outcomes through the role of workplace culture. Survey method is used for data collection. Partial Least Square (PLS) is used as data analysis on 100 samples of retail companies in West Java, Indonesia. The results show that performance appraisal effectiveness has a positive effect on workplace culture; workplace culture has a positive effect on employee outcomes (managerial performance and job involvement). The results also prove that workplace culture mediates the effect of performance appraisal effectiveness on employee outcomes. The study has practical implications that it is very important for organizations to consider the importance of a positive workplace culture when designing a performance appraisal system that is not only good but also effective in improving employee outcomes.Keywords: Performance appraisal effectiveness, employee outcomes, workplace cultureAbstrak. Penelitian ini bertujuan untuk menguji pengaruh efektivitas penilaian kinerja terhadap hasil kerja karyawan melalui peran budaya tempat kerja. Pengumpulan data menggunakan metode survei. Analisis data menggunakan Partial Least Square (PLS) pada 100 sampel perusahaan ritel di Jawa Barat, Indonesia. Hasil penelitian menunjukkan bahwa efektivitas penilaian kinerja berpengaruh positif terhadap budaya kerja; budaya tempat kerja memiliki pengaruh positif pada hasil karyawan (kinerja manajerial dan keterlibatan kerja). Hasil penelitian juga membuktikan bahwa budaya tempat kerja memediasi pengaruh efektivitas penilaian kinerja terhadap hasil kerja karyawan. Studi ini memiliki implikasi praktis bahwa sangat penting bagi organisasi untuk mempertimbangkan pentingnya budaya tempat kerja yang positif ketika merancang sistem penilaian kinerja yang tidak hanya baik tetapi juga efektif dalam meningkatkan hasil kerja karyawan.Kata kunci:Efektivitas penilaian kinerja, hasil kerja karyawan, budaya tempat kerja